Gender Differences in Use of Alcohol Treatment Services and Reasons for Nonuse in a National Sample. (26th February 2019) - Gilbert, Paul A.; Pro, George; Zemore, Sarah E.; Mulia, Nina; Brown, Grant
Abstract : Background: The majority of adults with alcohol use disorders do not obtain help, and women are less likely to utilize alcohol services than men. We sought to quantify gender differences in alcohol services utilization, overall and by type, using national longitudinal data and to explore potential gender differences in perceived need for help and reasons for not seeking help. Methods: We analyzed data from the National Epidemiologic Survey on Alcohol and Related Conditions from White, African American, and Hispanic adults ( n  = 2, 592) who met DSM‐IV criteria for alcohol abuse or dependence at Wave 1 (2000 to 2001). We tested gender differences in Wave 2 (2004 to 2005) services utilization, perceived need for help, and treatment barriers using Rao‐Scott chi‐square tests and assessed predictors of outcomes in multivariable logistic regression, adjusting for problem severity, co‐occurring disorders, and demographics. Results: Women had much lower odds than men of utilizing any alcohol service (adjusted odds ratio [aOR] 0.53; 95% confidence interval [95% CI]: 0.33, 0.86), specialty services (aOR 0.41; 95% CI 0.19, 0.87), and 12‐step groups (aOR 0.39; 95% CI 0.21, 0.71). Perceived need for help among those who had not used any services was very low (5%), with no gender difference. Further, men and women reported equivalent numbers of treatment barriers and the same rank order for the most frequently endorsed barriers. However, women were twice as likely as men to think a problem would get better by itself—the most frequent reason for not seeking help (47% vs. 24%, p  < 0.001), and men were more likely than women to report unsuccessful past help‐seeking and not thinking anyone could help (19% vs. 3%, p  < 0.001 and 17% vs. 5%, p  = 0.001, respectively). Conclusions: Consistent with previous studies, women were less likely to utilize alcohol services than men. Future interventions should address low problem recognition, and tailoring to gender‐specific barriers may help close the disparity in services utilization. Abstract : Analyzing national longitudinal data, women with AUD had much lower likelihood of using any services, specialty services, and 12‐step groups compared to men with AUD. Perceived need for help among those who had not used any services was very low (5%), with no difference by gender. Examining reasons for not seeking help, women were more likely to think a problem would get better by itself and men were more likely to report unsuccessful past help‐seeking and not thinking anyone could help.